Manipulating refractive index, homogeneity and spectroscopy of Yb$^{3+}$-doped silica-core glass towards high-power large mode area photonic crystal fiber lasers - Fan, Wang; Lili, Hu; Wenbin, Xu; Meng, Wang; Suya, Feng; Jinjun, Ren; Lei, Zhang; Danping, Chen; Nadège, Ollier; Guojun, Gao; Chunlei, Yu; And Shikai, Wang (Optics express, 2017)
Output power scaling of single mode large mode area (LMA) photonic crystal fiber (PCF) amplifiers urgently requires the low refractive index of Yb 3+-doped silica glasses whilst maintaining high optical homogeneity. In this paper, we report on a promising alternative Yb 3+ /Al 3+ /F-/P 5+-co-doped silica core-glass (YAFP), which is prepared by modified sol-gel method developed by our group and highly suitable for fabricating high power LMA PCF amplifiers. By controlling the doping combinations of Al 3+ /F-/P 5+ in Yb 3+doped silica glass,it not only ensures low refractive index (RI) but also maintains the excellent optical homogeneity and spectroscopic properties of Yb 3+. The spectroscopic properties of Yb 3+ ions have not deteriorated by the co-doping of Fand P 5+ in YAFP glass compared with that of Yb 3+ /Al 3+ co-doped silica glass. A large-size (⌀5 mm × 90 mm) YAFP silica-core glass rod with low average RI difference of 2.6 × 10 −4 (with respect to pure silica glass), and low radial and axial RI fluctuations of ~2 × 10 −4 , was prepared. A LMA PCF with 50 µm core diameter was obtained by stack-capillary-draw techniques using YAFP core glass. Its core NA is 0.027. An average amplified power of 97 W peaking at 1030 nm and light-light efficiency of 54% are achieved from a 6.5 m long PCF in the pulse amplification laser experiment. Meanwhile, quasi-single-mode transmission is obtained with laser beam quality factor M 2 of 1.4.